DEVELOPMENT OF A PROJECT BASED ONLINE LEARNING MODEL TO IMPROVE THE SKILLS AND ABILITIES OF ACTORS FOR STUDENTS - Suryandoko, Welly (PEDAGOGIK : JURNAL PENDIDIKAN, 2023)
This study describes the development process and feasibility of project-based online learning development to improve actorship abilities and skills for students of the Sendratasik Education Study Program, Faculty of Language and Arts, Surabaya State University. Using research methods, ADDIE development consists of 5 stages of implementation. The implementation stage of this research is only until development is carried out in the drama, dance, and music education study program with students consisting of one Sendratasik study program consisting of 3 traditional theater, actor, and educational theater courses. The research instruments are interview guidelines, expert validation instruments, questionnaires, and observation sheets. The improvement of abilities and skills developed has stages adjusted to the Project Based Online Learning model. There are six syntaxes of the Project Based Online Learning model: online product planning, designing online product planning, preparing online creation schedules, monitoring online project activity and development, testing work online, and evaluating online learning experiences. Based on the assessment of project-based online learning validators, the results of action on content suitability are high criteria, and aspects of construction and readability are very high.